Ultrasonic extraction of Clinacanthus nutans and its antioxidant activity - Nik Fatima, Nek Kamarzaman (2013)
explored antioxidant activity of Clinacanthus nutans (CN) and it was extracted by using ultrasonic-assisted extraction. Antioxidant activity of CN extract was determined by using free radical scavenging activity test and ferric reducing antioxidant power (FRAP) assay. Extraction process was carried out in ultrasonic bath at 28 kHz by using different solvent to solid ratio (ranging from 5mL/g to 50mL/g), temperature (ranging from 10 to 60 ºC), and sonication time (ranging from 0 min to 160 min). From result, it showed that the optimum extract of CN was obtained at 60 ⁰C, for extraction duration of 100 minutes with 10 mL/g liquor to solid ratio. The CN extract possessed antioxidant activity by scavenging DPPH with maximum effect of 61.08 %. The scavenging ability of CN extract has potency approximately 0.07 times of ascorbic acid. The CN extract also possessed reducing power to reduce ferric to its ferrous. 100 µg/mL of CN extract had same value of absorbance as 1.74µg/mL of ascorbic acid. This result proved that ferric reducing activity of CN extract was 57 times less powerful than ascorbic acid. In conclusion, antioxidant was extracted from Clinacanthus nutans by using ultrasonic extraction.